Report on citizenship law: East Timor (Timor-Leste) - Jerónimo, Patrícia (2017)
The Report focuses on the citizenship law of Timor-Leste. It provides an extensive historical background and discusses the main aspects of the current citizenship regime (including the modes of attribution, acquisition, and loss of Timorese citizenship), with recourse to primary (legislation and case law) and secondary sources.